Regenerative endodontics model in immature infected rat molars using two step protocol - Liliana Sierra; Ángeles Castrillo; Elizabeth Ritacco; Haydeé Miño Cornell; Mariela C Canzobre (Universidade Estadual de Campinas, 2021)
Aim: to develop a model for regenerative endodontics using newly-weaned Wistar rats immature molars with pulp necrosis to histologically describe the evolution of apical tissues following treatment with a bi-antibiotic paste, induced bloodclot formation and MTA. Methods: Ten 25-day-old female Wistar rats were divided into an initial control group (Ci) and two experimental groups in which pulp necrosis was experimentally induced on the left mandibular first molar by exposing the pulp chamber and leaving it open to the oral environment. One of the experimental groups was left untreated (E1) while the other was submitted to a protocol of regenerative endodontics 10 days thereafter (E2). Fifteen days after placement of a bi-antibiotic paste, bleeding was induced into the root canal space and MTA was placed upon. Animals were euthanized 30 days later. Right mandibular first molars served as an 80-day-old final control group (Cf). Each hemimandible was histologically processed to analyse parameters associated with root development. Statistical analysis was carried by means of ANOVA; p values below 0.05 were considered statistically significant. Results: baseline (i.e. 25-days old) mean root length and apical diameter of the distal root canal were 1.84±0.25 and 0.38±0.02mm respectively. Following the regenerative endodontic protocol, cells lining the walls of the root canal and significant increase to both length (2.37±0.22mm) and diameter (0.32±0.03 mm) were observed. Conclusions: newly-weaned Wistar rats serve as a suitable model to evaluate regenerative endodontic protocols. However, further research is needed in order to disclose the nature of the cells and/or cell mediators involved.